Analisis Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Purchase Decision (Studi Pada Konsumen Emina) - Nurul Fathihah Damarani; Widayanto Widayanto; Apriatni E Prihatini (Jurnal Ilmu Administrasi Bisnis, 2025)
Emina products are one of the cosmetic products that have experienced declining sales over the past five years, which are thought to be caused by online customer reviews and online customer ratings. This study aims to determine the effect of online customer reviews and online customer ratings on purchase decisions for Emina products. This type of research is an explanatory type of research, and the sample is taken using nonprobability sampling techniques and a purposive sampling approach with accidental sampling. Data collection was carried out by distributing questionnaires to 97 respondents. The results showed that there is a positive and significant influence between online customer reviews and purchase decisions, a positive and significant influence between online customer ratings and purchase decisions, and a significant influence between online customer reviews and online customer ratings simultaneously on purchase decisions. Based on these results, companies are advised to create a special platform containing reviews and ratings of products so as to facilitate the search for information about products and increase consumer purchasing decisions.Keywords: Online Customer Review; Online Customer Rating; Purchase DecisionProduk Emina adalah salah satu produk kosmetik yang mengalami penjualan yang penurunan penjualan selama lima tahun terakhir yang diduga diakibatkan oleh online customer review dan online customer rating.Penelitian ini bertujuan untuk mengetahui pengaruh online customer review dan online customer rating terhadap purchase decision produk Emina. Tipe penelitian ini adalah tipe penelitian eksplanatif dan sampel diambil menggunakan teknik nonprobablity sampling dan menggunakan pendekatan purposive sampling dengan accidental sampling. Pengumpulan data dilakukan dengan penyebaran kuesioner kepada 97 responden. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang positif dan signifikan antara online customer review terhadap purchase decision, pengaruh positif dan signifikan antara online customer rating terhadap purchase decision, serta pengaruh yang signifikan antara online customer review dan online customer rating secara simultan terhadap purchase decision. Berdasarkan hasil tersebut, perusahaan disarankan untuk membuat platform khusus berisi review dan rating terhadap produk sehingga mempermudah pencarian informasi mengenai produk dan meningkatkan keputusan pembelian konsumen.Kata Kunci: Online Customer Review; Online Customer Rating; Purchase Decision